Cores Produced by Geopolymer Technology and Impact to Casting Quality in Comparison with PUR Cold Box Amin - Vykoukal, Michal; Burian, Alois; Přerovská, Markéta; Luňák, Milan; Kyselka, Štefan (Manufacturing Technology Journal, 2019)
The article deals with geopolymer binder system for core production, especially by dehydration technology and comparison with PUR cold box amin technology. A sodium-potassium type of geopolymer binder is the subject of the research. The goal of the article is the core production and observing of technological properties, storing cores, usage of refractory coating evaluating of properties during the pouring and decoring of casting. The main target of the experiment is casting quality. It was stated that the final surfaces are much more better than PUR cold box amin technology and the internal casting quality is the same, it means without inadmissible internal defects. Worse decoring times were observed. It has been confirmed, that neither emissions, fumes nor unpleasant odours are generated during the production procedure nor during pouring.
Keywords: Geopolymer binder; Dehydration; Inorganic binder; Core; Environment